Experimental Investigation of Bacterial Inactivation of Beef Using Indirect Cold Plasma in Cold Chain and at Room Temperature - Peiru Li; Hainan Zhang; Changqing Tian; Huiming Zou (Foods, 2024)
Pathogen contamination is a severe problem in maintaining food safety in the cold chain. Cold plasma (CP) is a novel non-thermal disinfection method that can be applied for the bacterial inactivation of food in appropriate contexts. Currently, research on CP used on food at cold chain temperatures is rare. This work investigated the bacterial inactivation effect of CP on beef at typical cold storage temperatures of 4 and −18 °C and room temperature (25 °C). The reactive species in CP were indirectly tested by evaluating O3, NO3− and NO2− in cold plasma-activated water (PAW), which indicated the highest concentrations of reactive species in CP at 25 °C and the lowest at −18 °C. The bactericidal efficacy of CP treatment against beef inoculated with Escherichia coli at −18 °C, 4 °C, and 25 °C was 30.5%, 60.1%, and 59.5%, respectively. The 4 °C environment was the most appropriate treatment for CP against beef, with the highest bactericidal efficacy and a minor influence on beef quality. The indirect CP treatment had no significant effect on the texture, color, pH, or cooking loss of beef at −18 °C. CP shows significant potential for the efficient decontamination of food at cold chain temperatures.